Parent's knowledge and practices on selected aspects of Thalassaemia and factors related to defaulting treatment in relation to selected socio-demographic characteristics at National Thalassaemia Centre in Teaching Hospital Kurunegala - Ruwanpatbirana, T (My University, 2007)
Sri Lanka does not have a National preventive programme for Thalassaemia . Nevertheless, the government spends 5 percent of total health budget (which is a huge amount for a single disease) for the management of thalassaemics and every year around 100 patients are newly identified. Study-findings reveal that the parents of thalassaemics had a moderate knowledge about the disease and treatment and had a good knowledge about the prevention of the disease. They will be a good resource for future preventive programmes . Knowledge level was significantly associated with Sinhala ethnicity, Buddhist religion and with higher level of education. Nevertheless, knowledge about the bone marrow transplant as a mode of permanent cure was poor. Economic constrains was the main problem associated with defaulting treatment. Twenty-four parents (10.70/1 had more than one thalassaemic child and the main reason given for that was the inadequate counseling received. It is highly recommended to establish a National Thalassaemia preventive programme. Pre-marital testing of the carrier status should be advocated and necessary facilities should be made available. counseling of the parents of newly diagnosed thalassaemics should be established as a routine practice and details about all the methods currently available locally and globally should be conveyed to them in their mother tongue. ligation of internal iliac arteries; Post partum ligation and resection of tubes; Prim